2018
DOI: 10.1093/hmg/ddy257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel, methylation-dependent, RUNX2 regulatory region associated with osteoarthritis risk

Abstract: Osteoarthritis (OA) is a common, multifactorial and polygenic skeletal disease that, in its severest form, requires joint replacement surgery to restore mobility and to relieve chronic pain. Using tissues from the articulating joints of 260 patients with OA and a range of in vitro experiments, including CRISPR-Cas9, we have characterized an intergenic regulatory element. Here, genotype at an OA risk locus correlates with differential DNA methylation, with altered gene expression of both a transcriptional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…This suggests that the genetic association with various skeletal phenotypes might arise due to a difference in control of RUNX2 expression. Recent studies have shown that regulation of RUNX2 is tightly regulated by multiple epigenetic mechanisms, such as miR‐204/211 and other miRNAs, HDAC, and DNA methylation . Also, some of the genetic association signals near RUNX2 exert effects on epigenetics.…”
Section: Interpretation Of Epigenetic Studies: Problems and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the genetic association with various skeletal phenotypes might arise due to a difference in control of RUNX2 expression. Recent studies have shown that regulation of RUNX2 is tightly regulated by multiple epigenetic mechanisms, such as miR‐204/211 and other miRNAs, HDAC, and DNA methylation . Also, some of the genetic association signals near RUNX2 exert effects on epigenetics.…”
Section: Interpretation Of Epigenetic Studies: Problems and Toolsmentioning
confidence: 99%
“…Also, some of the genetic association signals near RUNX2 exert effects on epigenetics. For the osteoarthritis‐associated SNP, rs10948172, it has been shown to operate as a methylation quantitative trait loci (mQTL) for 4 CpG sites in the RUNX2 locus . Nevertheless, the GWAS signals are positioned at a relative large distance from RUNX2, and chromatin interaction from regulatory region to gene promoter is needed.…”
Section: Interpretation Of Epigenetic Studies: Problems and Toolsmentioning
confidence: 99%
“…These CpGs are known as methylation quantitative trait loci, or mQTLs. At several OA loci, including GDF5 and RUNX2, genotype at the associated SNP correlates not only with DNA methylation but also with gene expression 11,12 . This indicates that chondrocytes use DNA methylation as an intermediary between genotype and phenotype, with this epigenetic mechanism underpinning a large proportion of OA disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the progression of osteoarthritis was found to be accelerated in chondrocyte-specific Runx2-overexpressing mice [37]. Furthermore, methylation level of the RUNX2 gene has been correlated with the risk for osteoarthritis [38]. However, there is some debate regarding the pathogenic effects of RUNX2 in osteoarthritis because no reported evidence suggests the altered occurrence of osteoarthritis in patients with cleidocranial dysplasia compared with other populations (personal communication).…”
Section: Role Of Runx2 and Related Transcription Factors In Osteoarthmentioning
confidence: 99%